Stem cell-specific activation of an ancestral myc protooncogene with conserved basic functions in the early metazoan Hydra - Hartl, Markus (National Academy of Sciences, 2010)
The c-myc protooncogene encodes a transcription factor (Myc) with oncogenic potential. Myc and its dimerization partner Max are bHLH-Zip DNA binding proteins controlling fundamental cellular processes. Deregulation of c-myc leads to tumorigenesis and is a hallmark of many human cancers. We have identified and extensively characterized ancestral forms of myc and max genes from the early diploblastic cnidarian Hydra, the most primitive metazoan organism employed so far for the structural, functional, and evolutionary analysis of these genes. Hydra myc is specifically activated in all stem cells and nematoblast nests which represent the rapidly proliferating cell types of the interstitial stem cell system and in proliferating gland cells. In terminally differentiated nerve cells, nematocytes, or epithelial cells, myc expression is not detectable by in situ hybridization. Hydra max exhibits a similar expression pattern in interstitial cell clusters. The ancestral Hydra Myc and Max proteins display the principal design of their vertebrate derivatives, with the highest degree of sequence identities confined to the bHLH-Zip domains. Furthermore, the 314-amino acid Hydra Myc protein contains basic forms of the essential Myc boxes I through III. A recombinant Hydra Myc/Max complex binds to the consensus DNA sequence CACGTG with high affinity. Hybrid proteins composed of segments from the retroviral v-Myc oncoprotein and the Hydra Myc protein display oncogenic potential in cell transformation assays. Our results suggest that the principal functions of the Myc master regulator arose very early in metazoan evolution, allowing their dissection in a simple model organism showing regenerative ability but no senescence.